Analysis of the Antifungal Properties of Bacillus velezensis B-4 Through a Bioassay and Complete-Genome Sequencing - Zhu, Zheyuan; Peng, Qiong; Man, Yilong; Li, Zuren; Zhou, Xiaomao; Bai, Lianyang; Peng, Di (Frontiers in Genetics, 2020)
The strain B-4, isolated from a field in Changsha (China), presents strong antifungal activities, as identified by the Kirby-Bauer test, especially for pathogens that harm crops. Here, we obtained the complete genome sequence of the strain B-4 by Pacific BioSciences SMRT sequencing, making it well analyzed for understanding mechanisms and creating biological agents. Its 3,919-kb circular chromosome genome has 3,725 protein-coding genes (CDSs) and 46.7% GC content. A comparative genome analysis of B-4 with other published strains (including Bacillus velezensis, Bacillus amyloliquefaciens, and Bacillus subtilis) revealed that the strain B-4 is a B. velezensis strain. These different strains have 2,889 CDSs in common, whereas 179 CDSs were found to be unique in the strain B-4, which is a far greater number than that in other strains. Regarding the antifungal activities of B-4, we were specifically concerned with the genes involved in the biosynthesis of secondary metabolites. In total, more than 19.56% of the genome was annotated to 12 gene clusters relating to synthesisis of antimicrobial metabolites, which contained various enzyme-encoding operons for nonribosomal peptide synthetases (NRPS), polyketide synthases (PKS) and lantipeptide synthesis proteins. They were all considered to be related to the production of bacteriostatic substances or stimulation of induced systemic resistance by bacterial metabolites. These situations also present an advantage over those of other strains for biocontrol potential. We provide evidence that the biological control effect of the strain B-4, as demonstrated in antibacterial activity experiments and predicted from the complete genome sequence analysis, provides the basis for research promoting agricultural research on sustainable development, especially the contribution of biotechnology to agriculture.